Suppose $V$ is a finite-dimensional complex inner product space and $v_1,v_2,...,v_3$ is an orthonormal basis of $V$. Define $A:V \to V$ by $Av_i=\lambda_i v_i$ for some $\lambda_i \in \mathbb{C}.$ Show that $A^*v_i=\bar \lambda v_i.$

My attempt:

$(Av_i,v_i)=(\lambda_iv_i,v_i)=(v_i,\bar\lambda_i v_i)=(v_i,A^*v_i)$

$\Rightarrow(v_i,(A^*-\bar \lambda_i)v_i)=0 \Rightarrow (A^*-\bar \lambda_i)v_i \perp v_i $

How to show that $(A^*-\bar\lambda_i)v_i=0$ ?


Just extend what you have a bit: \begin{align} \langle \sum_j a_j v_j,A^*\sum_k b_k v_k \rangle = &\langle A \sum_{j}a_j v_j, \sum_{k}b_k v_k\rangle \\ = & \langle \sum_{j}\lambda_j a_j v_j,\sum_k b_k v_k\rangle \\ = &\sum_j\lambda_j a_j\overline{b_j} \\ = &\langle\sum_j a_j v_j,\sum_k \overline{\lambda_k}b_kv_k\rangle \\ \end{align}

  • $\begingroup$ @user1561 : Like the way I have redone it? $\endgroup$ – DisintegratingByParts Nov 16 '18 at 17:01
  • 1
    $\begingroup$ Yes. $\phantom{}$+1. $\endgroup$ – user1551 Nov 16 '18 at 17:23

Here is another method:

Let $M=[A]_\beta$, where $\beta=\{v_i\}_{1\le i\le n}$. Then $\det\,(M-\lambda I)=0\implies\det\,(M-\lambda I)^*=0$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.